Iowa Birdline update, February 19, 1990 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1990)
Notes for the Iowa Birdline update for February 19, 1990. Highlights of the update include sightings of an adult Lesser Black-backed Gull, an early Horned Grebe, an adult Tundra Swan, a Prairie Falcon, and a Pileated Woodpecker. Also of note was the return of an Evening Grosbeak to a feeder and a sighting of a Franklin's Gull in breeding plumage. Epson - sheet feed/flatbed